The educational experience at Politecnico di Torino to develop and increase the capability in aircraft layout comprehension and definition. Issue 1 (2nd January 2017) - Chiesa, Sergio; Fioriti, Marco; Fusaro, Roberta
Abstract: The aim of this paper is to present the recent experience in the education of Aircraft Engineers of a very peculiar aspect, the Airplane lay-out definition, in order to provide students at first with a global vision of the plane, the capability to operate in lay-out definition and to be conscious of such a context, clearly interfaced with all other design activities. At first, it is discussed how relevant and essential Aircraft Design Education is in a wider Aircraft Engineering Education context. Then it is described how Design is comprehensive for both Quantitative and Qualitative definitions, pointing out that Qualitative definitions, like an Airplane Layout (at a Subsystems level of the "block scheme" too), are extremely relevant but very difficult to acquire. So, an idea to start to educate young Engineers (PhD Students in particular) has been developed and, for the first time, has recently been held at our Politecnico. The organisation and the program of the course are described, with detailed attention to peculiar topics or practical exercises considered to be particularly useful to reach the educational objectives. In such a way a sort of logical guideline to starting to sketch an initial layout is acquired by the students. It is relevant how the undeniable interest generated by historic airplanes can be a powerful means to push Students to try to understand architectures and, eventually, to elaborate new solutions.